Randomized controlled trial of asthma risk with paracetamol use in infancy – a feasibility study. Issue 2 (February 2015) - Riley, J.; Braithwaite, I.; Shirtcliffe, P.; Caswell‐Smith, R.; Hunt, A.; Bowden, V.; Power, S.; Stanley, T.; Crane, J.; Ingham, T.; Weatherall, M.; Mitchell, E. A.; et al.
Summary Background There is non‐experimental evidence that paracetamol (acetaminophen) use may increase the risk of developing asthma. However, numerous methodological issues need to be resolved before undertaking a randomized controlled trial to investigate this hypothesis. Objective To establish the feasibility of a randomized controlled trial of liberal paracetamol as usually given by parents/guardians vs. a comparator (restricted paracetamol in accordance with WHO guidelines, ibuprofen or placebo), and childhood asthma risk. Methods Questionnaires were completed by parents/guardians of infants admitted to Wellington Hospital with bronchiolitis to assess views about comparator treatments. Subsequently, infants of parents/guardians who provided informed consent were randomized to restricted or liberal paracetamol use for 3 months with paracetamol use recorded. Results Of 120 eligible participants, 72 (60%) parents/guardians completed the questionnaire. Ibuprofen, restricted paracetamol and placebo were acceptable to 42 (58%), 29 (40%) and 9 (12%) parents/guardians, respectively. 36 (30%) infants were randomized to restricted or liberal paracetamol. Paracetamol use was greater for the liberal vs. restricted group for reported [Hodges–Lehmann estimator of difference 0.94 mg/kg/day (95% CI 0.2–3.52), P = 0.02] and measured use [Hodges–Lehmann estimator of difference 2.11 mg/kg/day (95% CI 0.9–4.18), P = 0.004]. The median reported and measured use of paracetamol was 2.0‐fold and 3.5‐fold greater in the liberal vs. restricted group. Conclusions and Clinical Relevance Although separation in paracetamol dosing is likely to be achieved with a liberal vs. restricted paracetamol regime, ibuprofen is the preferred comparator treatment in the proposed RCT of paracetamol use and risk of asthma in childhood.